Síntomas Depresivos en Estudiantes Universitarios y su Relación con el Uso Adictivo a las Redes Sociales (2023)
In the development of this research work, both general and specific objectives have been outlined to determine the relationship between depressive symptoms and the addictive use of social networks in a sample of university students belonging to the University of La Guajira, Maicao campus. Regarding the methodology, it was a quantitative approach, non-experimental design with cross-sectional correlational scope, in addition, programs such as EXCEL, JASP and SPSS were used for data treatment and analysis. The population was delimited through simple random sampling, obtaining a sample of 99 university students from the aforementioned headquarters. The psychometric instruments used were the Beck Depression Inventory (BDI-II) and the Social Media Addiction Questionnaire (ARS). The general result was achieved using Spearman's Rho statistician, obtaining a p<.01 and a correlation coefficient of 0.308, in addition to an ordinal regression analysis of p<.01 and a β= 0.824. Therefore, it was concluded that there is a low positive correlation between both variables in the population of the University of La Guajira, Maicao headquarters, and also that depression is a statistically significant predictor of social network addiction